Efektivitas Pelaksanaan Program Pemberdayaan Perempuan Kepala Keluarga (PEKKA) di Kabupaten Jombang - Utaminingsih, Alifiulahtin (IAIN Syekh Nurjati Cirebon, 2023)
ABSTRACT: This research analyzes how and effectiveness the Empowerment of Women Headed of Families (PEKKA) program is an empowerment program that involves women as the main target. This program was first introduced in 2000 as a